The syntax of Arabic - Aoun, Joseph (Cambridge syntax guides., 2010)
"Recent research on the syntax of Arabic has produced valuable literature on the major syntactic phenomena found in the language. This guide to Arabic syntax provides an overview of the major syntactic constructions in Arabic that have featured in recent linguistic debates, and discusses the analyses provided for them in the literature. A broad variety of topics are covered, including argument structure, negation, tense, agreement phenomena, and resumption. The discussion of each topic sums up the key research results and provides new points of departure for further research. The book also contrasts Standard Arabic with other Arabic varieties spoken in the Arab world. An engaging guide to Arabic syntax, this book will be invaluable to graduate students interested in Arabic grammar, as well as syntactic theorists and typologists"--Provided by publisher.